Is post-treatment standardized uptake value a prognostic factor in unresectable non-small cell lung carcinoma? - Ufuk Yılmaz; Yasar Zehra; Esra Korkmaz; Burcu Yalcın; Hakan Koparal; Engin Ozbilek (Medicinski glasnik, 2017)
Aim: Concurrent chemoradiotherapy (CRT) is the standard of care for locally advanced, unresectable non-small cell lung carcinoma (NSCLC). The aim of this study was to assess the prognostic value of maximum standardized uptake values (SUV max) in patients with unresectable stage III NSCLC treated with concurrent CRT. Method: 18 F-FDG PET-CT scans were obtained before and after treatment in patients with unresectable stage III NSCLC treated with concurrent CRT. To determine the prognostic value of SU-V max of the primary tumor (PT), univariate and multivariate Cox regression model were carried out. Results: Between January 2008 and December 2013, this study included 43 patients (median age 56 years, 95% male). Univariate analysis showed that having a high post-treatment PT-SU-V max was associated with a higher risk of death and having a high post-treatment PT-SUV max with a higher risk of disease recurrence. Multivariate analysis showed that having a low post-treatment PT-SUV max (cut off 3.9) was associated with longer overall and progression free survival (HR 8.55, 95% CI; 2.56-28.55, p=0.000 and HR 2.854, 95% CI; 1.43-5.67, p=0.003, respectively). Conclusion: Post-treatment PT-SUV max may be an independent prognostic factor in patients with unresectable stage III NSCLC treated with concurrent chemoradiotherapy.
Keywords: lung cancer; prognosis; positron emission tomography